Peran audit internal dalam meningkatkan kualitas laporan keuangan pada industri perbankan Indonesia - YENI JANUARSI; RIALIS RIALIS; NANA NOVIANTI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2016)
The purpose of this study is to test whether audit internal contribute in improving the qality of financial reporting in Indonesian banking industry. We measure Internal audit function by using the amount of internal audit activity reported to audit committee for a year, while financial reporting quality measure by accrual quality and timeliness. Purposive sampling methode is chose to collect sample from the banking industry. As a result, we obtained 68 firms-years observation, which represent 17 banks, for four years from 2009-1012. From hypothesis testing by using multiple regression, we find that internal audit function can not influence the accrual quality. In contrast, it has positive impact on timeliness. Our results suggest that internal audit, as part of CG mechanisme, play importat role for improving the quality of banking’s financial reporting.